Gedenkboek Lode Zielens 1901-1944 - Huysmans, Camille; Gilliams, Maurice; Mussche, Achilles; Herreman, Raymond; Minne, Richard; Schmook, Ger; Walschap, Gerard (Amsterdam Brussel : Elsevier, 1945)
Bibliotheek Camille Huysmans
Nederlands
Monografie
Keywords: Zielens, Lode; literatuur